The surface electromyographic evaluation of the Functional Reach in elderly subjects. (February 2016) - Maranesi, E.; Fioretti, S.; Ghetti, G.G.; Rabini, R.A.; Burattini, L.; Mercante, O.; Di Nardo, F.
Abstract: This study proposes a comprehensive assessment of myoelectric activity of the main muscles involved in the Functional Reach (FR) test, in 24 elderly subjects. A specific protocol for the surface electromyography (sEMG) signal acquisition during FR-test was developed. Results show that anterior muscles activate following a caudo-cranial order. Tibialis Anterior (TA) is the first to be activated (−18.0 ± 16.3% of the FR-period), together with Rectus Femoris (−10.4 ± 17.9%). Then, Rectus Abdominis (19.7 ± 24.7%) and Sternocleidomastoideus (19.9 ± 15.6%) activate after the FR-start. Hamstrings, Soleus, and L4-level Erectores Spinae (posterior muscles) activate after the FR-start in this order (11.4 ± 16.8%, 17.7 ± 16.6%, and 35.2 ± 29.0%, respectively) and remain active until the movement end. The analysis of the kinematic strategies adopted by subjects revealed an association between TA-activation patterns and two kinematic strategies (hip/mixed strategy), quantified by an increase ( p  < 0.05) of TA-activity duration in subjects adopting the hip strategy (89.9 ± 34.5) vs. subjects adopting the mixed strategy (27.0 ± 16.8). This suggests that TA sEMG activity could be able to discriminate among kinematic strategies, providing different information on balance control. Thus, the present analysis represents the first attempt to quantify the sEMG activity during FR-test in elderly subjects, providing an early contribution in building a reference frame for balance assessment in clinical context.